A Project Report on Enhancement of Fracture Life of Gas Turbine Wheel - SATISHA M (2007)
INTERNAL GUIDE: SANAL KUMAR V R, MVJCE EXTERNAL GUIDE: BABU S, STAFF ENGINEER, GAS AND WIND COMPONENTS
Keywords: Fracture Life of Gas Turbine Wheel